THE INFLUENCE OF COMPANY SIZE, AUDIT COMMITTEE AND AUDIT OPINION ON AUDIT REPORT LAG REGISTERED IN BANKING COMPANIES FOR THE 2019-2021 PERIOD - Suryanti, Dwi; Alliyah, Siti (Universitas Muhammadiyah Jember, 2024)
The interval between the financial report and the audit report is termed